Perancangan Sistem Monitorinng Suhu Under Counter Chiller Di Hotel Hilton Berbasis Internet of Things - Suriana, Wayan; Kase, Elvis; Adrama, I Nyoman Gede (Jurnal Ilmiah Telsinas, 2020)
Designing a system for long-distance temperature monitoring Under Counter Chiller in Hilton Hotel using IoT (Internet of Things) technology. The developed system consists of two parts; the controlling system and the monitoring system. First, the controlling system can turn on the hot air exhaust fan in the compressor system if the temperature in compressor part exceeds 40°C. This is to manage the temperature as wanted from the Under Counter Chiller chamber at Hilton hotel. Second, the monitoring system which can give information to the user real time. It will be easier and faster for the user to gain needed information related to the temperature being monitored at that very moment. From the temperature measurement made by the writer, it is obtained that the average temperature in chiller machine gained from the temperature measurer was 9.23 ºC. The average difference of temperature obtained from the temperature measurer was 0.38 ºC. The data was then sent by ATmega328 and ESP8266 Micro controller to the Web Server MyDevice Cayenne.